Pemanfaatan Perplexity.ai sebagai Instrumen Asesmen Diagnostik Produk Puisi Kelas VIII SMP - Ayu Setyowati, Putri; Sufanti, Main; Etika Rahmawati, Laili (Kajian Linguistik dan Sastra, 2024)
Diagnostic assessment is essential for teachers to determine the initial steps before learning begins. One useful instrument in this process is performance-based assessment, which evaluates products such as writing or other creative works. This study aims to describe the process and outcomes of diagnosing poetry products using the Perplexity.ai tool. Employing a qualitative descriptive method, the research analyzed 30 student poems collected as part of a diagnostic assessment of Indonesian language performance for class VIII H students at SMP Negeri 1 Salatiga. Data were gathered through initial observation and documentation of the Perplexity.ai application usage. Data analysis followed Milles and Huberman's interactive approach, encompassing data reduction, categorization, presentation, and conclusion drawing.The study found that (1) the Perplexity.ai application can be effectively utilized in learning, particularly for assessing students' poetry products. Teachers input students' poetry results into the application, specify the necessary assessment indicators, and allow the tool to evaluate the poems systematically. (2) The tool significantly aids teachers in analyzing student work, offering clear insights into key aspects. The diagnostic assessment results of students' poetry products highlighted three main evaluative aspects: rhyme, diction, and figures of speech. Overall, the Perplexity.ai application streamlines the diagnostic process and enhances the efficiency of evaluating student performance in poetry writing.